Ultrahigh‐Detectivity Photodetectors with Van der Waals Epitaxial CdTe Single‐Crystalline Films - Lian, Qin; Zhu, Xuanting; Wang, Xudong; Bai, Wei; Yang, Jing; Zhang, Yuanyuan; Qi, Ruijuan; Huang, Rong; Hu, Weida; Tang, Xiaodong; Wang, Jianlu; Chu, Junhao (Small (Weinheim an der Bergstrasse, Germany), 2019)
Van der Waals epitaxy (vdWE) is crucial for heteroepitaxy of covalence‐bonded semiconductors on 2D layered materials because it is not subject to strict substrate requirements and the epitaxial materials can be transferred onto various substrates. However, planar film growth in covalence‐bonded semiconductors remains a critical challenge of vdWE because of the extremely low surface energy of 2D materials. In this study, direct growth of wafer‐scale single‐crystalline cadmium telluride (CdTe) films is achieved on 2D layered transparent mica through molecular beam epitaxy. The vdWE CdTe films exhibit a flat surface resulting from the 2D growth regime, and high crystal quality as evidenced by a low full width at half maximum of 0.05° for 120 nm thick films. A perfect lattice fringe appears at the interfaces, implying a fully relaxed state of the epitaxial CdTe films correlated closely to the unique nature of vdWE. Moreover, the vdWE CdTe photodetectors demonstrate not only ultrasensitive optoelectronic response with optimal responsivity of 834 A W−1 and ultrahigh detectivity of 2.4 × 1014 Jones but also excellent mechanical flexibility and durability, indicating great potential in flexible and wearable devices. Direct epitaxy of wafer‐scale covalence‐bonded cadmium telluride (CdTe) thin films on 2D mica is achieved by molecular beam epitaxy. The CdTe/mica epitaxial films exhibit high single‐crystalline quality and well‐defined interfacial properties. The van der Waals epitaxy CdTe/mica photodetectors show ultrahigh detectivity and responsivity, and excellent mechanical flexibility and durability, indicating a great potential in flexible and wearable devices.